2010
DOI: 10.1021/jf101759x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Kinetics of β-N-Acetyl-d-glucosaminidase from Green Crab (Scylla serrata) by Zinc Ion

Abstract: Heavy metal pollution such as chromium and zinc in the seawater has been increasing in recent years in the China Sea. Marine shellfish such as prawn and crab are sensitive to this pollution. Beta-N-acetyl-d-glucosaminidase (NAGase, EC 3.2.1.52) catalyzes the cleavage the oligomers of N-acetylglucosamine (NAG) into the monomer. In this study, taking p-nitrophenyl-N-acetyl-beta-d-glucosaminide (pNP-NAG) as substrate, the effects of Zn(2+) on NAGase from green crab ( Scylla serrata ) have been studied. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In addition to altering the NAGase activity, the present study showed that both cadmium and zinc affected the protein content of the enzyme extracts. This could be linked to a particular “affinity” of these compounds to NAGase, NAGase degradation, which could be the reason for specific irreversible inhibitions that were observed in previous studies (Pan et al, 2007; Zhang et al, 2010). In addition, glyphosate displayed an inhibition of NAGase activity and affected protein content.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition to altering the NAGase activity, the present study showed that both cadmium and zinc affected the protein content of the enzyme extracts. This could be linked to a particular “affinity” of these compounds to NAGase, NAGase degradation, which could be the reason for specific irreversible inhibitions that were observed in previous studies (Pan et al, 2007; Zhang et al, 2010). In addition, glyphosate displayed an inhibition of NAGase activity and affected protein content.…”
Section: Discussionmentioning
confidence: 85%
“…However, the in vitro approach of NAGase alteration has been poorly investigated because the sampled crustaceans were weakly diversified (i.e., NAGase extracted from the Brachyura, S. serrata , or the Penaeide, L. vannamei ). Notwithstanding, these investigations revealed a direct alteration of NAGase by heavy metals (Lin, Wang et al, 2005; Lin, Xie et al, 2006; Yang et al, 2006; Zhang et al, 2010), antibiotics (Du et al, 2008; Yan et al, 2007), organic disinfectant agents (Lin et al, 2005; Xie et al, 2009), and amino acids (Xie et al., 2006). The sensitivity of NAGase activity has never been studied in caridean shrimps, which include several species of economical and ecological interests.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic studies were carried out by measuring enzyme activity at different concentrations of ABTS (50-10 0 0 μM) and NaCl (0-30 mM). The inhibition type was determined based on the Lineweaver-Burk plots as described [17] . The equilibrium constant K I for inhibitor (I) binding with enzyme (E) was obtained from the plot of the slopes of the LineweaverBurk curves versus NaCl concentrations.…”
Section: Determination Of Inhibition Mechanism Of Laccase By Naclmentioning
confidence: 99%
“…It is responsible for the degradation of chitin oligosaccharides into monomers that will be re-absorbed into the new cuticle (Espie and Roff, 1995). Several studies have shown that crustacean moulting and/or NAGase activity may be inhibited by exposure to endocrine disrupting compounds such as polychlorinated biphenyls (PCBs), pesticides, 4-octylphenol, diethylphthalate, and several metals (Xie et al, 2004;Zou, 2005;Meng and Zou, 2009;Zhang et al, 2010). Recently, the levels of epidermal NAGase activity in Carcinus maenas were shown to vary in relation to the moult cycle (Mesquita et al, 2011).…”
Section: Introductionmentioning
confidence: 98%